PENGARUH PERENDAMAN DAGING KAMBING DALAM BLEND JAHE (Zingiber Officinale Roscoe) PADA KONSENTRASI BERBEDA TERHADAP pH, DAYA IKAT AIR DAN SUSUT MASAK - Muhammad Luthfi Hidayat, Ali Husni, Dian Septinova dan Rr Riyanti (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2019)
This study aimed to determine the effect of soaking using ginger blend (Zingiber Officinale Roscoe) as a natural preservative on pH, water holding capacity, and cooking loss of goat meat. The experimental design used was completely randomized design (CRD) with 4 treatments and 5 replications. Goat meat used is thigh part as much as 20 pieces and the ginger used as blend is old ginger. The treatment in this study were P0: goat meat without soaking with blend of ginger, P1: soaked goat meat using a blend of ginger with a concentration of 5%, P2: goat meat soaked using a blend of ginger with a concentration of 10%, and P3: goat meat soaked using blend of ginger with concentration of 20%. The data obtained in this study were analysed with analysis of variance (ANOVA). The results showed that the length of soaking time using ginger blend ( Zingiber Officinale Roscoe) did not significantly affect the physical quality (pH, water holding capacity, cooking loss) of goat meat. Keyword: Concentration, Ginger (Zingiber Officinale Roscoe), pH, Water holding capacity, Cooking loss